2002
DOI: 10.1152/ajpregu.00766.2000
|View full text |Cite
|
Sign up to set email alerts
|

Sodium appetite and Fos activation in serotonergic neurons

Abstract: 2000.-We evaluated serotonergic hindbrain groups of cells for their involvement in the generation and inhibition of sodium appetite. For that purpose, we analyzed the number of Fos-immunoreactive (Fos-ir) cells and double-labeled Fosserotonin (5-HT)-ir neurons within different nuclei of the hindbrain raphe system and the area postrema (AP). Sodium depletion and sodium appetite were induced by peritoneal dialysis. Twenty-four hours after peritoneal dialysis, a 2% NaCl solution intake test was given to peritonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
62
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 40 publications
11
62
0
Order By: Relevance
“…Furosemide-induced sodium and water depletion enhanced the natriorexigenic response of IBO-DRN, which became significantly higher than that of PB-DRN only after 240 min of fluid offer, remaining at this level been shared by other investigators who have shown increased c-Fos expression in DRN serotonergic neurons after salt intake under both basal and sodium depletion conditions (11).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Furosemide-induced sodium and water depletion enhanced the natriorexigenic response of IBO-DRN, which became significantly higher than that of PB-DRN only after 240 min of fluid offer, remaining at this level been shared by other investigators who have shown increased c-Fos expression in DRN serotonergic neurons after salt intake under both basal and sodium depletion conditions (11).…”
Section: Discussionmentioning
confidence: 62%
“…Corroborating these findings, other investigators showed that basal c-Fos expression in serotonergic neurons of the DRN decreased after sodium depletion induced by peritoneal dialysis and increased after spontaneous and induced sodium intake, suggesting that there is a tonic inhibition of sodium appetite by serotonergic cells of this nucleus (11). Although we hypothesized the same, when working with DRN electrolytic lesion it is necessary to limit the lesion to the neuronal cell body located in the ventromedial portion of the DRN and to perform longer observations (21).…”
Section: Introductionmentioning
confidence: 68%
“…The SFO and OVLT constitute convergent sites for signals related to volume depletion (4,18,28,29). As mentioned previously, these structures are innervated by serotonergic neurons, are rich in serotonin receptors and reciprocally transmit signals to the raphe (1,2,4-6,8).…”
Section: Discussionmentioning
confidence: 95%
“…Recent evidence has shown that sodium depletion induced by the combination of furosemide with a low dose of captopril causes an increase in c-Fos expression in the nucleus tractus solitarii (NTS), which is suppressed by renal deafferentation (31). Following the same line of reasoning, evoked potentials were recorded in serotonergic neurons of the DRN after the isoosmotic loss of volume by hemorrhage and, more specifically, induction of c-Fos expression was determined in serotonergic neurons of the DRN and in structures of the lamina terminalis after sodium depletion by peritoneal dialysis (7,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation